MELAYU PATTANI THAILAND: MUSLIM MINORITY RELIGION EXPRESSION IN THE MIDDLE OF NON MUSLIM MAJORITY - Arismunandar, Arismunandar; Afriantoni, Afriantoni; Asmuni, Asmuni (Universitas Islam Negeri Raden Fatah Palembang, 2019)
Pattani Province in southern Thailand is the only province with the majority of the Muslim population. Besides Pattani the majority of Thai residents (67 million people) are Buddhists. Only 10% of Thai people are Muslims, including Pattani's Muslim Malay minority. Some data suggest that the Thai government made policies that often discredited and did not accommodate the interests of Malay Muslims. This became one of the reasons for the emergence of opposition to Thai government and ethnicity. For example, must use the Thai language (thaification Program) reinforced by the prohibition of the use of Malay language and nationalization of Thai society culture through language and customs. The cultural policies relating to the use of Thai language and customs are intended to promote Thai nationalism, while they erode the identity (religion and culture) of Pattani Malay. The Malay minority resistance was led by the scholar Tuan Guru Haji Sulong Al-Fathani. He also acted as negotiator with the Thai government in order to fight for Malay Muslim aspirations. His negotiations resulted in a policy of the enactment of Malay language education as a curriculum material at Pattani National School.